Association between nutritional status and outcome of childhood acute lymphoblastic leukemia treated with Wijaya Kusuma Protocol - Fransiska Herintya; Sri Mulatsih; Endy Paryanto Prawirohartono (Indonesian Pediatric Society Publishing House, 2008)
Background Acute lymphoblastic leukemia (ALL) is the most common malignancy in childhood. Malnutrition in malignancy patients including ALL is one of major problems. This condition is found at the time of diagnosis as a result of the disease itself or after, chemotherapy or radiation. Many studies have been conducted to determine the relationship between nutritional state and outcome of childhood ALL patients but the result was still controversial. Objective To determine relative risk of death and relapse in childhood standard-risk ALL who received therapy using Wijaya Kusuma protocol. Methods This was a retrospective cohort study. Newly-diagnosed patients since May 1999-December 2004 were taken for this study. Body mass index was used to measure nutritional status for >2 years old children, and weight-for-height was used for those of =2 years old. Data was obtained from Yogyakarta Pediatric Cancer Registry Dr. Sardjito Hospital. Chi-squared test was used to analyze the proportion difference and risk relative was used to determine risk for death and relapse. Results One-hundred and forty five patients included in this study. There was no association between nutritional state and relapse (RR 1.1, 95% CI 0.76;1.61). Logistic regression analysis showed that there was association between nutritional state and death (RR 2.34, 95% CI 1.01;5.45). Sepsis and relapse have contribution to death as well (RR 6.75, 95% CI 2.9;15.4 and RR 3.2, 95% CI 1. 3;8.08 respectively). Conclusion Nutritional status is not associatiated with relapse but is associated with death of ALL children.